Paper/Pencil Versus Online Data Collection: An Exploratory Study - Ward, Peter; Clark, Taralyn; Zabriskie, Ramon; Morris, Trevor (Journal of leisure research, 2014)
Usage of online data-collection methods are increasing in leisure research. Some potential benefits to using online methods over traditional paper/pencil techniques include financial savings and easier access to large populations. Disadvantages, however, include difficulty in sample selection and variations of the instruments' reliability. This study explores how subject responses potentially differ when collecting data online versus paper/pencil for six instruments commonly used within leisure research. A repeated measure design with paired sample t-tests and HLM was used with 207 college students to compare these methods of data collection. Responses differed between methods on three of the tested instruments. A general pattern was found suggesting participants perceived their anonymity was better protected when completing online questionnaires.